Etiology, Sensitivity and Resistance Pattern of Urinary Tract Infection Among Children (0 To 16 Years) - Manoj Kumar, Warda Khalid, Amin Ali, Syed Khurram Sajid, Yumna Aslam, Ayaz Ur Rehman (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine etiology, sensitivity and resistance pattern of urinary tract infection in pediatrics age group 0 to 16 years at tertiary care hospital. Methodology: It was a cross-sectional study conducted inPediatric department of Aga khan university hospital and its affiliated secondary care centers in Karachi and Hyderabad. All urine culture proven children aged 0-16 years were included in the study. Urine culture showed growth of single pathogen and pathogen had more 10,000 colonies. Urine samples were obtained by SPA, clean catch, urinary catheter. Pre-designed proforma was used to note down the etiology and resistance pattern of urinary tract infection. SPSS version 25 was used to analyse data. Results: Of 177 patients, 70.1 % were females and 29.9% were males. Most common organism was E.coli 71.2% (n=126) followed by Klebsiella pneumonia 16.9% (n=30). Proteus Mirabilis 6.8% (n=12), and Pseudomonas aeruginosa 5.1% (n=9). Most common organism E.coli was 78% and 72.7% sensitive to nitrofurantoin and amikacin respectively and 85.1%, 91.4% and 77.3% resistance to ceftriaxone, ciprofloxacin and ampicillin respectively. This study will help in choosing choice of antibiotic on empirical basis for better outcome in resources limited setting like in remote areas and reduced financial burden on community. Conclusion: E.coli was the most common bacterial isolates among children with UTI. Nitrofurantoin and Amikacin showed higher sensitivity against E.coli., while Ciprofloxacin, Ceftriaxone and Ampicillin showed high resistance against E.coli. Keywords: Bacterial resistance, E.coli, urinary tract infection, paediatric population, antimicrobial sensitive